Understanding of groundwater evolution through chemical and age dating information in the Yongding River alluvial fan in Beijing - Liu, Kai; Qiao, Xiaojuan; Wang, Shanshan; Sun, Ying (Frontiers in Environmental Science, 2022)
The Yongding River (YDR) is the mother river of Beijing, and several urban water supply sources and observated wells are located along the river. Identifying the characteristic of sediment and groundwater in the YDR alluvial fan is helpful for groundwater uses and protection. To explore the evolution process of groundwater and sediment, the typical profile from Mentougou to Fengheying is chose to analyze, which represents one of the most typical hydrogeological units in YDR alluvial fan. The analysis results show that: (i) Along the profile, the contents of coarse grain gradually decrease while fine particles regularly increase. Meanwhile, the similar evolution trend is found in the vertical direction. (ii) The annual renewable rate of groundwater is > 10% in the upper fan, 2%–8% nearby Daxing, and < 2% in Fengheying, respectively. (iii) In the proximal-fan area, the average flow velocity of single and double layer is about 65 m·yr-1 and of approximately 18.9 m·yr-1, respectively. From the mid-fan to distal-fan, the value of velocity and hydraulic conductivity decreases from 12.4 m·yr-1 to 3.75 m·yr-1, and from 8.54 m·yr-1 to 0.64 m·yr-1, respec-tively. (iv) The water-chemistry type gradually changes from HCO3-Ca·Mg to HCO3-Na. Under-standing the evolution process of sediment and hydrochemistry in the YDR alluvial fan can help learning the similar hydrogeological units in the alluvial fan region of northern China.